The process of increasing the EU dependence on the security guarantees of NATO (1999-2004) - Ćuprić Damjan S. (Baština)
The article aims to demonstrate that, with the adoption of the Maastricht Treaty, the EU expressed a clear intention and aspiration to build its geopolitical ambition. This ambition positioned the EU to develop a security and defense policy and make it operationally capable. The article traces the evolution of the CSDP EU, following its development toward operational capability, up to the accession of CEE countries to the EU. In this way, the EU managed to threaten the dominance of NATO's security guarantees, which until then were exclusive and unquestionable. The practical establishment of the CSDP culminated in April 2003 at the Summit of France, Germany, Belgium, and Luxembourg, where the creation of an EU military planning headquarters for European autonomous action was agreed upon. The argument of the founding states of the EU is emphasized: that first it is necessary to have a stronger and more unified Europe in defense within NATO, as a prerequisite for greater military and economic participation of Europe in NATO. The article highlights a paradox: by achieving operational capability of the CSDP, the EU, in practice, increased rather than reduced its reliance on NATO's security guarantees, which was initially one of its primary objectives. It can be concluded that the 1999 NATO bombing of the FRY shows that strategic decisions are more influenced by events than by "theoretical commitments." NATO's expansion towards CEE countries exposed divisions within the EU. While the EU contributes economically to these states, the same cannot be said for security, leading to long-lasting stagnation in EU integration in the area of security and defense, a situation which is still ongoing.